LEKSIKON ETNOMEDISIN DALAM PENGOBATAN TRADISIONAL MINANGKABAU - Almos Rona; Pramono pramono (Masyarakat Linguistik Indonesia Universitas Andalas, 2015)
System of traditional medicine to this day is still alive, although the practices of modern medicine is growing rapidly with the emergence of centers of government and private health services. The phenomenon Back to Nature (back to nature) are increasingly intensified by the developed countries have a positive impact on the flourishing of the traditional medical systems. The method used to analyze the data are unified method. Unified method used is equivalent translational methods and methods of unified referential. In this study lexicon Minangkabau traditional medicine can be classified into three groups: the types of diseases, types of herbs and treatment process.